The Development Guidelines on Local Wisdom Scholar for Promote Community-Based Tourism at Rong Wua Daeng San Kamphaeng Chiang Mai Province - Jaipeng, Chanistha; Pitsawaeng, Chai (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this study were; 1) to study the context of local scholars to promote Community-based Tourism, 2) to study the process of local scholars in transferring local wisdom to strengthen communities, and 3) to give a guideline for the potential development of local scholars to promote Community-based Tourism at Rong Wua Daeng San Kamphaeng Chiang Mai Province. This study was a qualitative method integrated with a documentary, focus group discussions, and an in-depth interview method. The population of this research was purposely selected consisting of local scholars, community leaders, monks, government representatives, students, and people with a grand amount of 75 people. Data analysis using descriptive statistics and then presented with descriptive writing. The results revealed that; 1) context of local scholars for promoting Community-based Tourism at Rong Wua Daeng was found that there were 5 main points: (1) a social knowledge source; (2) a cultural leader and the way of life in the community; (3) a transferring knowledge to the community; (4) being an innovator from wisdom, and (5) a role player in the community’s strengthening process in terms of beliefs, practices, traditions, rituals, livelihoods and folk nutrition, folk health care, folk technology, and biodiversity management, 2) the process of transferring wisdom with lectures oral telling, demonstrations, real practice, the use of media for the self-learning process, the transmission through folk performances and local traditions including recording the body of knowledge in textbooks, and 3) guidelines for developing the potential of local philosophers in promoting community-based tourism in Rong Wua Daeng Sub-district, San Kamphaeng District Chiang Mai Province (1) Skill Potential Development (2) Knowledge Potential Development (3) Personality Potential Development.